Transformation of school assessment. Approaches within an educational innovation process: A cross-case analysis of schools in Catalonia (Spain) - David Martinez Maireles (Ricerche di Pedagogia e Didattica)
This study aims to characterize transformations in assessment approaches accompanying inclusive educational innovation processes. A multiple case study design was employed to examine assessment framework modifications in seven Catalan schools undertaking significant pedagogical reform initiatives. Semi-structured interviews and document analysis explored shifts in evaluation paradigms at both the institutional and classroom levels, encompassing organizational and curricular elements. While changes at both levels were investigated, the current paper focuses exclusively on modifications at the school level. The findings indicate an urgent need for increased collaborative and coordinated work among educators. A key result highlights the necessity of realigning assessment practices to be congruent with transformations to instructional philosophies and methods. This exploratory cross-case synthesis provides new insights into an under-studied facet of reform efforts with relevant implications for the strategic development of balanced evaluation models that facilitate sustainable curriculum innovations on a long-term basis.